Corn Substitution By Using Cassapro (Cassava Protein) On Kampung Chicken Carcass - Hans Yoppi Sinaga, Iskandar Sembiring; Armyn Hakim Daulay; Ma’ruf Tafsin; Nevy Diana Hanafi (Talenta Publisher, 2019)
This research aimed to determine the ability of cassapro to substitute corn in feed onkampung chicken carcass. Experimental design used was completely randomized design (CRD) with5 treatments and 4 replications. Each treatment consists of cassapro P0 (0%) P1(10%) P2(20%)P3(30%) P4(40%). 100 kampung chicken was used this research.The results showed that there were no signifiant effect on cut weight, carcass weight and percentageof carcass due to the administration of cassapro. However, there was a tendency that feed rations P2(40% corn and 20% cassapro) showed good result.